A cautionary note on synonymization based on mitochondrial data in Orthoptera: a comment of Hochkirch et al. 2023 - Nabholz, Benoit; Puissant, Stéphane; Defaut, Bernard (Zootaxa, 2024)
Hochkirch et al. (2023) recently published a phylogeny of the band-winged grasshopper genus Oedipoda. Using three mitochondrial and one nuclear loci, they estimated the phylogeny of 177 specimens. This phylogeny offers insights into the evolutionary history and biogeography of the group and demonstrates the usefulness of molecular data to estimated populations and species histories. They also provide valid taxonomical changes, raising two former subspecies and one former synonymy to the species level. However, we believe that taxonomic changes regarding synonymization proposed by the authors are premature given the data utilized. Indeed, we will illustrate cases below where well-established species lack support from mitochondrial data, which is comparable to or even more extensive than that used by Hochkirch et al. (2023).